Simulation of membrane separations using a modified Maxwell-Stefan model - Brito, Paulo (2010)
In this work, a modified Maxwell-Stefan model, which considers both the concentration polarization and the transport through the membrane, is tested for the simulation of Dextran T70 aqueous solutions filtration. Numerical simulations by solving the model equations with an adaptive resolution algorithm, based on the Adaptive Method of Lines, determined the concentration profiles in the polarization layer and inside the membrane pore. It is shown that the formation of significant solute accumulation at the membrane/polarization interface leads to high levels of apparent rejection. A tubular cross-flow ultrafiltration module, containing a tubular polysulfone membrane with a molecular weight cut-off of 50 kDa, was used to perform the experiments. The model is able to successfully simulate data in the high rejection/low flux region using an equilibrium constant Keq of 0.25, but does not reproduce the observed rejection drop/pressure build-up which occurs for increased fluxes, which may be due to limitations of the model itself.